Evaluation of Character Education in Public High School Using the CIPP Model - Gusti Ayu Putu Budi Aryati; Dewa Gede Hendra Divayana; I Gede Ratnaya (Jurnal Pendidikan dan Pengajaran, 2023)
Character education becomes one of the contemporary concerns nowadays. This study aims to analyze the character education program at Public High School by using the CIPP model evaluation. Data in this study were collected through questionnaires, observation and documentation. The collected data was processed by univariate analysis with quantitative descriptive method. The results of the data analysis showed that the effectiveness of the character education program at Public High School from the four types of respondent groups all indicated the very effective category. The first group of educator respondents in the category is very effective in terms of the Context variable 88.20% of the Input variable of 81.27%, of the Process variable of 87.11% and of the Product variable of 81.65% simultaneously producing (+++ +). The second group of education staff respondents in the very effective category in terms of the Context variable is 85.66.% of the Input variable is 86.11%, the Process variable is 91.25% and the Product variable is 93.75% simultaneously producing (+ +++). The third group of student respondents in the very effective category in terms of the Context variable 91.78% of the Input variable of 86.63%, of the Process variable of 82.73% and of the Product variable of 86.66% simultaneously produce (++ ++). Furthermore, the fourth group of committee respondents in the very effective category in terms of the Context variable 82.08% of the Input variable of 83.71%, of the Process variable of 72% and of the Product variable of 89.15% simultaneously produces (++++).